Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Suryamas Cipta Perkasa II Desa Paduran Sebangau Kecamatan Sebangau Kuala - Lidya Hutabarat; Kalvin Anggen; Murniati Murniati (Jurnal Manajemen Sains dan Organisasi, 2020)
Purpose, - The purpose of this research is to know how much the influence of work motivation and job satisfaction on the employee performance of PT. Suryamas Cipta Perkasa II Village of Paduran Sebangau subdistrict Sebangau Kuala.Design/methodology/approach - The research methods used are descriptive statistics and multiple regression statistics. Findings - This study shows partial results (test-t): a) Work motivation is influential and significant towards employee performance, B) job satisfaction is influential and significant to employee performance, and simultaneously the results of the study show Work motivation and job satisfaction have significant effect on employee performance of variable donations in this study of R2 = 0.493 or 49.3%.